45307 雙曲線上相異四點的斜率相關不變量

### 二、本文

\begin{align*} m_{\overline {AB}}=&-\frac ba\!\times\! \frac{(e^{t_1}-e^{t_2})-(e^{-t_1}-e^{-t_2})}{(e^{t_1}-e^{t_2})+(e^{-t_1}-e^{-t_2})}=-\frac ba\!\times \! \dfrac{(e^{t_1}-e^{t_2} )- \frac{e^{t_2}-e^{t_1}}{e^{(t_1+t_2)}}}{(e^{t_1}-e^{t_2})+ \frac{e^{t_2}-e^{t_1}}{e^{(t_1+t_2)}}}\\ =&-\frac ba\!\times\! \dfrac{1+e^{-(t_1+t_2)}}{1-e^{-(t_1+t_2)}}, \\ &\dfrac{\frac ab\times m_{\overline {AB}}+1}{\frac ab\times m_{\overline {AB}}-1} %=\dfrac{\Big[\frac 2{(1-e^{-(t_1+t_2)} )}\Big]}{\Big[\frac{2e^{-(t_1+t_2)}}{1-e^{-(t_1+t_2)}}\Big]} =e^{(-t_1-t_2)}=e^{-t_1}\times e^{-t_2}=F(A)\times F(B)\hbox{。} \end{align*}

\begin{align*} m_{\overline {AB}}=&\frac ba\!\times\! \frac{(e^{t_1}-e^{t_2})-(e^{-t_1}-e^{-t_2})}{(e^{t_1}+e^{t_2})+(e^{-t_1}+e^{-t_2})}=\frac ba\!\times \! \dfrac{(e^{t_1}-e^{t_2} )+ \frac{e^{t_1}-e^{t_2}}{e^{(t_1+t_2)}}}{(e^{t_1}+e^{t_2})+ \frac{e^{t_1}+e^{t_2}}{e^{(t_1+t_2)}}} =\frac ba\!\times\! \dfrac{e^{t_1}-e^{t_2}}{e^{t_1}+e^{t_2}}, \\ &\dfrac{\frac ab\times m_{\overline {AB}}+1}{\frac ab\times m_{\overline {AB}}-1} %=\dfrac{\Big[\frac 2{(1-e^{-(t_1+t_2)} )}\Big]}{\Big[\frac{2e^{-(t_1+t_2)}}{1-e^{-(t_1+t_2)}}\Big]} =-e^{(t_1-t_2)}=-e^{t_1}\times e^{-t_2}=-F(A)\times F(B)\hbox{。} \end{align*}

$$\Big(\dfrac{\frac ab\times m_{\overline {AB}}+1}{\frac ab\times m_{\overline {AB}}-1}\Big)\times \Big(\dfrac{\frac ab\times m_{\overline {AC}}-1}{\frac ab\times m_{\overline {AC}}+1}\Big)=\frac{F(B)}{F(C)}\times \hbox{sign}(B,C),$$

$$\Big(\dfrac{\frac ab\times m_{\overline {DB}}+1}{\frac ab\times m_{\overline {DB}}-1}\Big)\times \Big(\dfrac{\frac ab\times m_{\overline {DC}}-1}{\frac ab\times m_{\overline {DC}}+1}\Big)=\frac{F(B)}{F(C)}\times \hbox{sign}(B,C),$$

### 參考文獻

hyperbola-Wikipedia。

---本文作者郭品增、蔡一全、連家堯投稿時為彰化高中二年級學生---